STRATEGI PEMASARAN YANG TEPAT UNTUK MENINGKATKAN PENJUALAN USAHA ES DAWET AYU MAS TOMI ASLI BANJARNEGARA DIPINGGIRAN JALAN SM RAJA MEDAN, SUMATERA UTARA - Fanny Julia Putri; Putri Nurhayati; Shofwan Hafiz Siregar; Zainarti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Es Dawet Ayu Mas Tomi is a traditional beverage made from natural ingredients such as coconut, rice flour, palm sugar, and pandan leaves. The unique taste and texture of this dawet are its main attractions. This dawet is packaged in convenient and hygienic packaging, suitable for consumption in any setting. Competitive pricing with appropriate profit margins is a crucial factor in the marketing strategy. With affordable prices yet maintaining good quality, Es Dawet Ayu Mas Tomi can attract more consumers. The strategic location on the outskirts of SM Raja Street, near schools, and other activity centers, facilitates consumer access to enjoy this product. Moreover, availability at several sales points also expands the market reach. Promotion Effective promotion is key to increasing consumer awareness and interest in the product. Through various promotion channels such as social media, collaboration with local influencers, and cooperation with stores or stalls in the vicinity, Es Dawet Ayu Mas Tomi can expand its market share and increase sales